UMP and Indonesia’s Polytechnics LP31 forged strategic alliances - UMP, PNC
Universiti Malaysia Pahang (UMP)’s ICT Business Centre signed memorandums of understanding (MoU) with three Polytechnic LP 31s and a high school from Indonesia, marking another milestone in the close relationships enjoyed both by Malaysia and its neighbor country, Indonesia.